Atlas of Global Development, 4th Edition : A Visual Guide to the World's Greatest Challenges - World Bank (Glasgow: Collins Bartholomew for the World Bank, 2013)
COMPLETELY REVISED AND UPDATED Published in association with Harper Collins, the completely revised and updated fourth edition of the Atlas of Global Development is a comprehensive guide to the most critical issues facing our changing world today.